The Role of Task, Relationship, and Process Conflicts in Shaping Employee Performance in Nepal’s Commercial Banks - Shrestha, Arbind; Singh, Balgopal (International Research Journal of Parroha, 2024)
This study aims to assess the impact of workplace disputes—specifically those related to tasks, relationships, and procedures—on the performance of workers at commercial banks in Nepal. The banking sector, characterized by hierarchical structures and intense environments, is particularly susceptible to various forms of conflict. A standardized questionnaire was administered to 200 respondents across different departments of commercial banks, employing a quantitative approach. Correlation and regression analyses were conducted using SPSS to investigate the relationship between workplace disagreements and employee performance. Results indicate that all three types of workplace conflicts—task, interpersonal, and process conflicts—significantly adversely affect employee performance. A moderately negative correlation was found between task conflict and performance (r = -0.45), suggesting that unresolved disagreements can hinder productivity despite potentially fostering discussion. Interpersonal conflict showed a considerable negative impact on performance (B = -0.65), indicating that strained relationships undermine team cohesion and morale. Process conflict significantly affected workflow efficiency (F = 6.82, p = 0.005). The study also revealed that employee experience moderates the relationship between task conflict and performance, with more experienced employees managing conflicts more effectively. These findings underscore the need for tailored conflict resolution strategies to mitigate the negative effects of workplace disputes.